Synesthesia on Our Mind - Marks, Lawrence E.; Mulvennad, Catherine M. (Theoria et Historia Scientiarum, 2014)
Synesthesia in perception and metaphor in language both provide ways to categorize and comprehend the world. Both operate through mechanisms that capitalize on the creation or discovery of links across disparate domains – notably, sensory experiences in different modalities, with cross-modal correspondences serving as perceptual links in synesthesia and as conceptual links in metaphor. The perceptual links in synesthesia are typically fixed and rigid. The conceptual links in metaphor, however, enable meanings to expand, creatively, through the active construction of novel, emergent relations: Metaphors transform meanings, thereby transcending the fixed correspondences of synesthesia. Recent evidence associates the presence of synesthesia with an augmented capacity for creative cognition. Other evidence associates synesthesia with neural hyperconnectivity – augmented connectivity between regions of the cerebral cortex that process the synesthetically linked domains. We suggest that mechanisms underlying synesthesia may also play a role in processes that foster creative transformations of meanings in metaphor.